Correction to: Erythrocyte concentrations of chromium, copper, manganese, molybdenum, selenium and zinc in subjects with different physical training levels. Issue 1 (14th April 2021) - Maynar, M.; Grijota, F. J.; Siquier-Coll, J.; Bartolome, I.; Robles, M. C.; Muñoz, D.
Abstract : An amendment to this paper has been published and can be accessed via the original article.